δ13C as indicator of soil water availability and drought stress in Pinus radiata stands in South Africa - Fischer, Phillip Murray (Stellenbosch : University of Stellenbosch, 2011)
Thesis (MSc (Forest and Wood Science))--University of Stellenbosch, 2011.